DROPBOX PAJAK SEBAGAI INOVASI BARU PELAYANAN PERPAJAKAN UNTUK MENGOPTIMALKAN PENERIMAAN PAJAK - ULA, CHAMIDATUL (Jurnal Akuntansi AKUNESA, 2013)
Taxes general directorate doing innovation newing to optimize taxesacceptance. That innovation which is as dropbox taxes. To the effect ofobservational it which is to know taxes acceptance before and after marks sensedropbox's facility. What accepting that have reached optimal result. Dropbox isplace forwarding SPT yearly for income tax, and income tax acceptance becomeslargest contribution deep accepting taxes as a whole. Before marks sense dropboxtaxes, taxeses accepting realization each year average under 95% of budgettargets. Meanwhile afters marks sense dropbox accepting realization taxes taxeseach year upon 96% of budget targets.Keywords : Dropbox, taxes acceptance, income tax.